Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x-51)=2.8+20 b) 4.(x-3) = 49-1 c) 2x-49=5.27 d) 9.(x+4)-25=5.4
x-51 =16+20 4.(x-30)=48 2x-49=135 9.(x+4)-25=20
x-51 =36 x-30=48:4 2x =135+49 9.(x+4) =20+25
x = 36+51 x-30= 12 2x =184 9.(x+4) =45
x = 87 x =12+30 x=42 x =184:2 x= 92 x+4 =45:9
x+4 =5
x =5-4 x=1
1.
a. Ta có: \(A=2^{300}=2^{3.100}=\left(2^3\right)^{100}=8^{100}\)
\(B=3^{200}=3^{2.100}=\left(3^2\right)^{100}=9^{100}\)
Mà \(8^{100}< 9^{100}\)
\(\Rightarrow A< B\)
b. Ta có: \(A=2^{332}< 2^{333}=2^{3.111}=\left(2^3\right)^{111}=8^{111}\)
\(B=3^{223}>3^{222}=3^{2.111}=\left(3^2\right)^{111}=9^{111}\)
Mà \(8^{111}< 9^{111}\)
\(\Rightarrow A< B\)
c. Ta có: \(A=2^{91}=2^{13.7}=\left(2^{13}\right)^7=8192^7\)
\(B=5^{35}=5^{5.7}=\left(5^5\right)^7=3125^7\)
Mà \(8192^7>3125^7\)
\(\Rightarrow A>B\)
Câu 2:
a: =>(x-6)(x-7)=0
=>x=6 hoặc x=7
b: =>\(x^8\left(x^2-25\right)=0\)
\(\Leftrightarrow x^8\left(x-5\right)\left(x+5\right)=0\)
hay \(x\in\left\{0;5;-5\right\}\)
32 ( x + 14 ) - 52 = 5 x 22
9 ( x + 14 ) - 25 = 5 x 4
9( x +14 ) - 25 = 20
9 ( x +14 ) = 45
x + 14 = 5
x = -9
32 ( x+ 14 ) - 52 = 5 x 22
9 ( x + 14 ) - 25 = 20
9( x + 14 ) = 20 + 25 = 45
x + 14 = 45 : 9 = 5
x = 5 - 14 = -9
chúc học tốt
\(a,\left(7x-11\right)^3=2^5.5^2+200.\)
\(\left(7x+11\right)^3=32.25+200.\)
\(\left(7x+11\right)^3=800+200.\)
\(\left(7x-11\right)^3=1000.\)
\(\left(7x-11\right)^3=10^3.\)
\(\Rightarrow7x-11=10.\)
\(\Rightarrow x=\left(10+11\right):3=7\in Z.\)
Vậy.....
\(b,3^x+25=26.2^2+2.3^0.\)
\(3^x+25=26.4+2.\)
\(3^x+25=104+2.\)
\(3^x+25=106.\)
\(3^x=106-25.\)
\(3^x=81.\)
\(3^x=3^4\Rightarrow x=4\in Z.\)
Vậy.....
\(c,2^x+3.2=64.\)(có vấn đề).
\(d,5^{x+1}+5^x=750.\)
\(5^x.5^1+5^x+1=750.\)
\(5^x\left(5^1+1\right)=750.\)
\(5^x\left(5+1\right)=750.\)
\(5^x.6=750.\)
\(5^x=750:6.\)
\(5^x=125.\)
\(5^x=5^3\Rightarrow x=3\in Z.\)
Vậy.....
\(e,x^{15}=x.\)
\(\Rightarrow x\left(x^{14}-1\right)=0\Rightarrow\left\{{}\begin{matrix}x=0\\x=1\end{matrix}\right..\)
\(f,\left(x-5\right)^4=\left(x-5\right)^6.\)
\(\Leftrightarrow\left(x-5\right)^4-\left(x-5^6\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left[1-\left(x-5\right)^2\right]=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left(1-x+5\right)\left(1+x-5\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left(6-x\right)\left(x-4\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4=0\Rightarrow x-5=0\Rightarrow x=5\in Z.\)
\(6-x=0\Rightarrow x=6\in Z.\)
\(x-4=0\Rightarrow x=4\in Z.\)
Vậy.....
52x-3-2.52=52.3
52x-3-50=75
52x-3=75+50
52x-3=125
=>52x-3=53
=>2x-3=3
=>2x=6=>x=3
\(2240\div\left(x-5\right)=2^2\times5^2-20\)
\(\Rightarrow2240\div\left(x-5\right)=4\times25-20\)
\(\Rightarrow2240\div\left(x-5\right)=80\)
\(\Rightarrow x-5=2240\div80\)
\(\Rightarrow x-5=28\)
\(\Rightarrow x=28+5=33\)